Estimating pneumococcal vaccine coverage among Australian Indigenous children and children with medically at-risk conditions using record linkage. Issue 12 (19th March 2021) - Kabir, Alamgir; Newall, Anthony T.; Randall, Deborah; Menzies, Rob; Sheridan, Sarah; Jayasinghe, Sanjay; Fathima, Parveen; Liu, Bette; Moore, Hannah; McIntyre, Peter; Gidding, Heather F.
Abstract: Background: Risk-based recommendations are common for pneumococcal vaccines but little is known about their uptake. In Australia, pneumococcal conjugate vaccine (PCV) was funded only for Aboriginal or Torres Strait Islander (Indigenous) children and those with underlying medical conditions in 2001, and then there were different booster dose recommendations depending on risk after the introduction of universal PCV vaccination in 2005. Methods: We measured coverage of PCV dose 3 and additional PCV and 23-valent pneumococcal polysaccharide vaccine (PPV23) doses by risk group among children born in July 2001–December 2012 in two Australian states using linked immunisation and hospitalisation data (available until December 2013). We ascertained medical risk conditions using hospitalisation diagnosis codes and Indigenous status using an established algorithm, comparing coverage for children born pre (2001–2004) and post (2005–2012) universal PCV funding. Results: Among 1.3 million children, 63, 897 (4.9%) were Indigenous and 32, 934 (2.5%) had at least one medically at-risk condition identified by age 6 months. For births in 2001–2004, coverage for PCV dose 3 by 1 year of age was 37% for Indigenous, 15% for medically at-risk and 11% in other children, increasing to 83%, 91% and 92%, respectively for births in 2005–2012. In children with medically at-risk conditions, PCV dose 4 coverage by 2 years was 1% for 2001–2004 births, increasing to 9% for 2005–2012 births, with PPV23 coverage by 6 years 3% in both cohorts. Among eligible Indigenous children, PPV23 coverage by 3 years was 45% for 2001–2004 births and 51% for 2005–2012 births. Conclusions: Coverage with additional recommended booster doses was very low among children with medical conditions, and only modest among Indigenous children. If additional PCV doses are recommended for some risk groups, especially in the context of routine schedules with reduced doses (e.g. 2 + 1 and 1 + 1), measures to improve implementation will be required.